The Effect of Financial Literacy on MSME Financial Management in the Gunungpring Religious Tourism Area - Sijabat, Yacobo P; Hirawati, Heni (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2026)
MSMEs play a strategic role in the Indonesian economy, yet many business owners continue to face challenges in managing business finances, particularly in financial recording, reporting, control, and the separation of personal and business finances. This study aims to analyze the effect of financial literacy on the financial management of MSME actors in the Gunungpring religious tourism area, Magelang. Gunungpring provides an important research context because MSME activities in this area are shaped by the characteristics of religious tourism businesses, including daily cash transactions, fluctuating tourist visits, and strong social and family-based economic practices. This study employed a quantitative approach with a causal research design. Convenience sampling was applied due to limited access to respondents during the tourist season. The sample consisted of 30 MSME actors. Primary data were collected using a five-point Likert-scale questionnaire. Financial literacy was measured through indicators of financial knowledge, financial behavior, financial attitude, and financial capability. Financial management was measured through indicators of financial planning, financial recording, financial reporting, financial control, and separation of personal and business finances. The data were analyzed using validity and reliability tests, classical assumption tests, simple linear regression, coefficient of determination, and t-test. The results show that financial literacy has no significant effect on MSME financial management, as indicated by a significance value of 0.228 > 0.05. The Adjusted R Square value of 0.017 indicates that financial literacy explains only 1.7% of the variation in financial management. These findings suggest that MSME financial management in the Gunungpring religious tourism area may be more strongly influenced by factors outside the model, such as business experience, family habits, access to informal capital, and mutual-help practices.